PSYCHOLOGICAL WELL-BEING PADA REMAJA PANTI ASUHAN DI KOTA BANDA ACEH - Fitri, Bella Anugrah; Amna, Zaujatul (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2016)
Life in the orphanage can affect adolescentsâ€™s living conditions, such as psychological well-being. Psychological well-being is affected by many factors, there are life experience,age, social support, religiosity and gender. The sampling technique used was purposive sampling. The participants were 74 adolescents (337males and 37 females), with aged range between 14-18 years who lived at the orphanages in Banda Aceh city. The data collected by using Ryffâ€™s Psychological well-being Scale revisited with coefficient realibility 0,935. The study showed there was adoloscents of orphanages with high category psychological well-being (97,3%).The results of data analysis used Independent Sample T-Test with significant value (Ï) = 0,036 (Ï < 0,05) and corelation dimension of psychological well-being used Pearson. The study showed that there was difference psychological well-being between males and females and then six dimension of psychological well-being contribute for psychological well-beingâ€™s adoloscent of orphanages in Banda Aceh city